Using video-notational analysis to examine soccer players` behaviours - Caso, S.; Furley, P.; Jordet, G. (International Journal of Sport and Exercise Psychology, 2026)
The purpose of numerous scientific disciplines is to comprehend human behaviour. However, much of human behaviour that is understood to date occurs in artificial laboratory settings. Although this approach allows researchers to control variables, it is limited in understanding human behaviour in natural, fast and high pressure performance environments like soccer. Video-notational analysis could address these limitations by providing behavioural observations, following constructionist perspectives that argue that understanding behaviours in context - relative to environments and relationships - is fundamental. Accordingly, this conceptual paper explores the use of video-notational analysis to examine players` behaviours in soccer, particularly emotions, visual exploratory activity (VEA) and intra-team communication. These topics were selected by the technical staff of Ajax AFC as they could provide immediate video inputs to the team and individual players about their psychological performance. The paper reviews previous literature on the use of video-notational analysis in understanding these players` behaviours and its potential contributions to the field of sport psychology and performance analysis for future research, integrating emerging technologies such as artificial intelligence (AI), machine learning as well as practical implications and reflections.